Euthanasia: National and international experience (based on the European Court of Human Rights practice materials) - Olena O Orlova; Tetiana M Alforova; Tetiana M Lezhnieva; Stanislav V Chernopiatov; Oleh V Kyrychenko (Wolters Kluwer Medknow Publications, 2023)
Purpose: The relevance of the study is that today, there is no unanimous position on the right to euthanasia implementation. The European Court of Human Rights (ECtHR), in making its decision, relies on the national legislation of the respective state, as there is no single decision on the right to euthanasia in the European space. Therefore, the aim of the article is to comprehensively study the phenomenon of euthanasia, elaborate the decisions of the ECtHR on euthanasia and related rights, and develop recommendations on the possibility of legalizing euthanasia in Ukraine and prospects for the right to die implementation. Methodology: The leading method of research of this issue is comparative and law, which allows to comprehensively consider the right to euthanasia and its positive and negative components and helps to establish trends in the implementation of the outlined phenomenon. Findings: The article analyzes the current state of international and domestic legislation of some states on the use of euthanasia, reveals the meaning of the term "euthanasia," provides a classification of euthanasia, analyzes the decisions of the ECtHR, and presents examples of national legislation of states within which euthanasia is legalized, the peculiarities of euthanasia recognition in the world are analyzed, as well as the research on the possibility of euthanasia legalization in Ukraine is presented. Value: The materials of the article have practical value for all those interested in euthanasia and the realization of the right to die, as well as for practicing lawyers and judicial authorities.